Type II collagen expression is regulated by tissue-specific miR-675 in human articular chondrocytes. - Dudek, K; Lafont, J; Martinez-Sanchez, A; Murphy, C (2010)
miRNAs have been shown to be essential for normal cartilage development in the mouse. However, the role of specific miRNAs in cartilage function is unknown. Using rarely available healthy human chondrocytes (obtained from 8 to 50 year old patients), we detected a most highly abundant primary miRNA H19, whose expression was heavily dependent on cartilage master regulator SOX9. Across a range of murine tissues, expression of both H19- and H19-derived miR-675 mirrored that of cartilage-specific SOX9. miR-675 was shown to up-regulate the essential cartilage matrix component COL2A1, and overexpression of miR-675 rescued COL2A1 levels in H19- or SOX9-depleted cells. We thus provide evidence that SOX9 positively regulates COL2A1 in human articular chondrocytes via a previously unreported miR-675-dependent mechanism. This represents a novel pathway regulating cartilage matrix production and identifies miR-675 as a promising new target for cartilage repair.